Influence of Aluminum Incorporation on the Adsorptive Performance of Silica-Based Supported Sulfonic Acid for the Chemical Recovery of Gaseous O-Xylene - Yaxu Wang; Jiaxuan Chai; Yining Li; Zichuan Ma (Molecules)
A group of silica-based supports with varying Al/Si ratios (S−x) was synthesized using the sol–gel method, followed by a chlorosulfonic acid modification to produce supported sulfonic acids (SA−x). The S−x and SA−x materials, along with their adsorption products, were characterized via techniques such as FTIR, BET, and HPLC-MS. The analysis revealed that the sulfonic acid groups in the SA−x materials existed in two anchoring states: the covalently bonded (CB) state [SiOx–O]ɗ−–SO3Hɗ+ and the ion-paired (IP) state AlOy+:OSO3H−. The sulfonation reactivity of the CB-state sulfonic acid was enhanced, whereas that of the IP-state counterpart was diminished. The incorporation of a minor quantity of aluminum ions (x = 0.1) markedly enhanced the adsorption efficiency of SAs for o-xylene, extending the reaction temperature range to 110–190 °C and increasing the breakthrough adsorption capacity (QB) to 946.1 mg g−1. However, excessive aluminum ion incorporation was detrimental to the adsorption performance of SAs for o-xylene. SA−0.1 showed superior adsorptive capabilities and excellent recyclability, maintaining its performance over four consecutive adsorption/regeneration cycles with only a minor decrease of 4.5%. These findings suggest that SAs prepared with a minor amount of aluminum ions have significant potential for application as adsorbents for the removal of benzene series pollutants.